2019
DOI: 10.1002/ijc.32249
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a cycle‐specific risk score for febrile neutropenia during chemotherapy cycles 2–6 in patients with solid cancers: The CSRFENCE score

Abstract: The absolute risk reduction by prophylaxis in chemotherapy‐induced febrile neutropenia (FN) is largest in patients at highest underlying risk. Therefore, reliable predictive models are needed. Here, we develop and validate such a model for risk of FN during chemotherapy cycles 2–6. A prediction score for risk of FN during the first cycle has recently been published. Patients with solid cancers initiating first‐line chemotherapy in 2010–2016 were included. Cycle‐specific risk factors were assessed by Poisson re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…We observed FN incidence of 32.8% overall in patients without G-CSF prophylaxis, which is higher compared to most reports. [11,12,21] However, Nishikawa et al observed even higher incidence (39.5%).…”
Section: Discussionmentioning
confidence: 96%
“…We observed FN incidence of 32.8% overall in patients without G-CSF prophylaxis, which is higher compared to most reports. [11,12,21] However, Nishikawa et al observed even higher incidence (39.5%).…”
Section: Discussionmentioning
confidence: 96%
“…Considering the complexity of risk factors for FN, there has been an effort to develop risk scores capable of predicting the risk for individual patients. Several studies developed risk scores for FN [55][56][57][58][59], some of which have been prospectively validated [56,58]. The overview of these studies, including independent risk factors for FN, is shown in Table 2.…”
Section: Risk Scores For Febrile Neutropeniamentioning
confidence: 99%
“…Aagard et al introduced an internally validated risk score for FN during the first cycle of chemotherapy (the FENCE Score) [57]. Recently, an update providing cycle-specific risk for FN (during cycle 2-6) in solid tumors has been published [59]. Such risk scores could be used to predict the risk of FN in a particular patient and initiate preventive measures, including the use of G-CSF in high-risk patients, although external validation in large prospective trials is required [59].…”
Section: Risk Scores For Febrile Neutropeniamentioning
confidence: 99%
“…Recently, a risk score ("FENCE" score) for febrile neutropenia after chemotherapy has been made available, both at the first cycle of chemotherapy 39 and for cycles 2-6 in patients with solid cancers. 40 Non-hematological toxicity is not-so-easy to predict, yet, the CARG score and the CRASH score can be highly helpful. 17,18 Thus, one major practical recommendation for all older patients being considered for cytotoxic chemotherapy is to use these, or other disease-specific CGA-based prognostic scores, to estimate risk of toxicity from chemotherapy, and refrain from using cytotoxic chemotherapy if risk of toxicity is higher than 40% and not preventable, that is, by using prophylactic Granulocyte Colony-Stimulating Factor (G-CSF) and/or reducing dose/intervals in palliative setting.…”
Section: How Can Toxicity Be Prevented?mentioning
confidence: 99%
“…Recently, a risk score (“FENCE” score) for febrile neutropenia after chemotherapy has been made available, both at the first cycle of chemotherapy 39 and for cycles 2‐6 in patients with solid cancers 40 …”
Section: Practical Suggestionmentioning
confidence: 99%